2DAM-WAVE : um método de avaliação para o modelo de capacidade wave - Glanzner, Rafael Audy (2012)
The Global Software Development (GSD), has been used by various companies around the world. To help these companies overcome the difficulties imposed by this type of work, the WAVE capability model was proposed. However, until the conclusion of this research, it was not possible to use the WAVE effectively in the industry, since there was none assessment method for it. This research proposes an assessment method for the WAVE capability model, and it is called 2DAM-WAVE. It allows organizations that wish to implement the best practices of WAVE, find out in which capability level they are situated. To propose this method a qualitative analysis of the existent assessment methods was made, after this, the assessment method was applied in a Brazilian unit of a global organization and on an Indian unit from another organization, by conducting of two case studies. As a result of this research an assessment method for the WAVE, entitled 2DAM-WAVE, and a support tool that helps and facilitates this assessment were developed